Job Motivation of Communal Public Servants An Empirical Study in Hanoi - Mai, Nguyễn Phương; Hảo, Hoàng Văn (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 31 No 5E, 2015)
Abstract: In the administration system of Vietnam, the communal government is the lowest level but it has a very important role. Communal servants are the key factor that determines the efficiency and effectiveness of the public administrative system at the grassroots level. The results of their civil service, in turn, depend mostly on their moral qualities, expertise, responsibility, attitude and job motivation. Hanoi is the capital of Vietnam with different characteristics from other provinces in the country. These characteristics significantly influence the job motivation of the civil public servants. This paper presents the results of an empirical study in My Duc district, Hanoi, to clarify the factors that play the role of job motivators of the public servants. Thus, some suggestions are raised to foster the job motivation of communal public servants. Keywords: Job motivation, communal public servants.